Pengaruh Beban Kerja dan Lingkungan Kerja Terhadap Turnover Karyawan Gen Z Studi Kasus pada UMKM di Kabupaten Toraja Utara - Helda Yosep; Stefani Marina Palimbong; Dina Ramba (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Helda Yosep, 2025, "The Influence of Workload and Work Environment on  Gen Z Employee Turnover: A Case Study on MSMEs in North Toraja Regency". The purpose of this study is to find out whether there is an influence of workload and work environment on  Gen Z employee turnover A case study on MSMEs in North Toraja Regency. The data collection procedure from this study is: Observation, Questionnaire and Documentation.The method used in this study is a quantitative method using the Multiple Linear Regression method and processed using SPSS 26. The researcher took samples using survey techniques with samples taken from MSME employees in North Toraja Regency consisting of 100 respondents. Calculation results in the t-test Workload t calculated 6.366 > t table 1.664, With a sig value of 0.000> 0.05. And in the variable Work Environment t calculate 6.366 > t table 1.664, with a sig value of 0.000> 0.05. The conclusion of this study is that Workload Affects  Gen Z Employee Turnover and Work Environment Does Not Affect  Gen Z Employee Turnover in North Toraja Regency.